The systematic status of Amblyphrynus Ingeri (Amphibia: Leptodactylidae) With the description of an allied species in western Colombia The systematic status of Amblyphrynus Ingeri (Amphibia: Leptodactylidae) With the description of an allied species in western Colombia - Lynch John D. (Caldasia)
Amblyphrynus ingeri es una especie representada hasta ahora solamente por tres ejemplares, todos coleccionados en la Cordillera Oriental de Colombia.  Nuevo material demuestra que Amblyphrynus es inseparable del grupo sulcatus de Eleutherodactylus. El grupo sulcatus contiene cinco especies: E. helonotus, E. ingeri, E. maussi, E. sulcatus, y una nueva especie que se describe en este trabajo con base en ejemplares provenientes de las Cordilleras Central y Occidental. La nueva especie y E. ingeri son los miembros más avanzados de este grupo de especies, y estan estrechamente relacionadas con E. sulcatus, una especie amazónica. Amblyphrynus ingeri is known from three specimens, all collected on the Cordillera Oriental of Colombia. New material reveals that Amblyphrynus is inseparable from the sulcatus group of Eleutberodactylus. The sulcatus group contains five species: E. helonotus, E. ingeri, E. maussi, E. sulcatus, and a new species described herein on the basis of specimens from the Cordilleras Central and Occidental. The new species and E. ingeri are the most derived members of the species group and form a tight cluster with E. sulcatus, an Amazonian species.